Drivers of Purchase Intention in Local Culinary Businesses: The Role of Price, Location, and Promotion - Faizul Muttaqin; Arimbawa, Putu Adi Putra (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Consumer purchase intention is a crucial factor for business sustainability and growth amid increasingly intense market competition. Therefore, this study aims to determine whether price, business location, and promotion influence consumer purchase intention toward Nyotoo.gang products. This explanatory quantitative research targeted residents of Magelang City who are aware of the Nyotoo.gang business, with a total sample of 120 respondents. The statistical analysis involved instrument testing, classical assumption tests, multiple linear regression, and hypothesis testing using SPSS 25 for Windows. The results showed that price has a positive and significant effect on purchase intention, business location has a positive and significant effect on purchase intention, and promotion also has a positive and significant effect on purchase intention.